Multimorbidity patterns and mortality in older adults: Results from the KORA-Age study - Arshadipour, Ava; Thorand, Barbara; Linkohr, Birgit; Ladwig, Karl-Heinz; Heier, Margit; Peters, Annette (Frontiers in Nutrition, 2023)
The coexistence of chronic diseases has created major difficulties for older adults, making it crucial to understand multimorbidity (MM) patterns and associated mortality. We aimed to determine the prevalence of MM and common chronic disease combinations, as well as their impact on mortality. The baseline chronic disease status of the participants was determined in the KORA-Age study in 2008/9, and mortality status was determined until 2016. MM was defined as having at least two chronic diseases. We used Cox proportional hazard models to calculate the hazard ratios (HRs) with 95% CIs for associations between MM and all-cause mortality. 495 men (24.6%) and 368 women (17.4%) died during the study period. Although the MM prevalence was almost the same in men (57.7%) and women (60.0%), the overall effect of MM on mortality was higher in men (HR: 1.81, 95% CI: 1.47-2.24) than in women (HR: 1.28, 95% CI: 1.01-1.64) (P-value for interaction <0.001). The type of disease included in the MM patterns had a significant impact on mortality risk. For example, when both heart disease and diabetes were included in the combinations of two and three diseases, the mortality risk was highest. The risk of premature death not only depends on the number of diseases but also on the disease types included in the MM patterns. To prolong life expectancy in older adults, it may be crucial to address the most significant MM-related diseases, such as diabetes, hypertension, and heart disease.